Lung ultrasound for the diagnosis of subpleural consolidations - a review of the veterinary and human literature - Michał Gajewski (Acta Veterinaria Scandinavica)
Abstract Lung ultrasound (LUS) is an imaging modality of growing importance in human medicine. LUS has been extensively applied to human patients. Guidelines have been created for internal medicine, describing ultrasonographic features of various lung pathologic processes. Such guidelines do not exist for veterinary medicine, and studies on the utility of LUS in companion animals are limited. Therefore, this review compares conclusions from veterinary studies to recommendations in human medicine for the detection of subpleural consolidations beyond the application of LUS as a point-of-care modality in emergency and critical care.